2001
DOI: 10.1056/nejm200105173442004
|View full text |Cite|
|
Sign up to set email alerts
|

Replacement of an Avulsed Phalanx with Tissue-Engineered Bone

Abstract: From the Center for Tissue Engineering (C.A.V., L.J.B., M.P.V.); the Departments of Anesthesiology (C.A.V., L.J.B., M.P.V.), Cell Biology (L.J.B.), and Pathology (M.P.V.); and the Division of Plastic Surgery (J.S.) -all at the University of Massachusetts Medical School, Worcester. Address reprint requests to Dr. Charles A. Vacanti at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
160
0
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(167 citation statements)
references
References 35 publications
1
160
0
6
Order By: Relevance
“…Periosteal cells have been widely used in bone tissue engineering by isolating osteoprogenitor cells from the patient's periosteum and seeding them into bioresorbable scaffolds [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Periosteal cells have been widely used in bone tissue engineering by isolating osteoprogenitor cells from the patient's periosteum and seeding them into bioresorbable scaffolds [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The scaffold is used for its osteoconductive properties [7,8] and the cells or growth factors are used for their osteoinductive or osteogenic properties [9,10]. While successful in vivo studies [11,12] and in clinical studies [13], this strategy has difficulties to settle in routine clinical practice. The reasons are manifold but often related to the cost, the stringent regulations established by the regulatory authorities, the specialized infrastructure needed, or the lack of possible reimbursement from health insurances when cells or growth factors are employed.…”
mentioning
confidence: 99%
“…Vacanti et al (2001) reported successful tissue engineering of the distal phalanx, to replace this bone in a patient who suffered partial avulsion of the thumb. However, only 25% of the normal strength was obtained.…”
Section: Treatment Of Bone Lossmentioning
confidence: 99%